PERANCANGAN SISTEM INFORMASI USULAN KENAIKAN PANGKAT DAN JABATAN FUNGSIONAL DOSEN - Karnila, Sri (Jurnal Informatika, 2007)
Aim of the research is to design information system for Penetapan Angka Kredit (PAK) of functional Lecture grade based on computerized system. This system produces a report of PAK, and has facilities for data entry and searching, so that, it produces of information: accuracy, timelines, and relevancy. This research uses paradigm of system development life cycle, shish covers the activities of gathering data through observation, interview and literature study; system analysis uses flow map ; system design uses context diagram, data flow diagram, data dictionary, entity relationship diagram, file relationship, file structure, program structure, input design, output design and menu structure.